Realizing Religious Harmony in Tura Village Through the Establishment of The Balai Basarah Worship Place for The Hindu Kaharingan Faith - Herliani (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2024)
The aim of this research is to promote harmony between religious communities through a moderate approach and ensure that all citizens can carry out their worship in accordance with their beliefs. This research was carried out in accordance with the PAR (Participatory Action Research) Method as an approach to developing as many control substances as possible by the village. The method used includes a field survey to identify the needs and preferences of religious communities in Tura village regarding worship facilities. After conducting a survey and obtaining data on the condition of Tura village, there is an urgent need to do this, namely developing an attitude of caring between religious communities in society. With this survey, a superior program was produced that focuses on religious moderation, namely by implementing a superior program in the form of providing a special prayer hall for Kaharingan Hindu believers. The program to provide special prayer halls for Hindu Kaharingan religious communities can also be a forum for developing solutions to support diversity and social harmony in the archipelago. In this superior program, the idea of ​​providing a hall for the Kaharingan Hindu community was implemented by utilizing the Tura village meeting hall which had not been used for a long time. The meeting hall then evolved to involve village officials, youth organizations and religious leaders.